All-Atom Model of Atactic 2-Vinyl Pyridine Polymer: Structural Properties Investigation by Molecular Dynamics Simulations. Issue 9 (1st January 2019) - Caputo, Stefano; De Nicola, Antonio; Donati, Greta; David, Alessio; Raos, Guido; Milano, Giuseppe
Abstract : Atactic poly(2-vinyl pyridine) (P2VP) is widely used in several 3D-Printing applications, in blends or, as one of the blocks, in copolymers. Moreover, several applications have been designed by exploiting the stimuli response to the pH shown by P2VP. In this paper we propose an all atom model of P2VP, based on the well-known OPLS-AA force field, which ensures wide compatibility to model complex mixtures and/or interfaces involving P2VP in composite materials. The proposed all-atom model was checked in the reproduction of structural properties and compared with experimental data. Good reproductions of mass density and X-ray scattering pattern confirm the accuracy of the proposed model.